2016
DOI: 10.1186/s12875-016-0415-1
|View full text |Cite
|
Sign up to set email alerts
|

Multicentric randomized clinical trial to evaluate the long-term effectiveness of a motivational intervention against smoking, based on the information obtained from spirometry in primary care: the RESET study protocol

Abstract: BackgroundSpirometry is the recommended method of evaluating pulmonary function when respiratory disease is suspected in smokers. Nonetheless, no evidence exists of the usefulness of information obtained from this test as a motivational strategy for smoking cessation. The primary objective of this study is to evaluate the effectiveness of a motivational intervention based on spirometry results in achieving long-term smoking cessation.Methods/DesignWe propose a multicenter randomized clinical trial in the prima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 44 publications
(57 reference statements)
0
9
0
Order By: Relevance
“…RESET is a multicentre randomized controlled clinical trial carried out in 20 primary health care centres in the province of Tarragona (Spain), aimed to evaluate the 12-month effectiveness of an intervention providing structured information about the results of spirometry in prolonging smoking abstinence rates [22]. This trial has been registered with ClinicalTrial.gov (NCT02153047).…”
Section: Methodsmentioning
confidence: 99%
“…RESET is a multicentre randomized controlled clinical trial carried out in 20 primary health care centres in the province of Tarragona (Spain), aimed to evaluate the 12-month effectiveness of an intervention providing structured information about the results of spirometry in prolonging smoking abstinence rates [22]. This trial has been registered with ClinicalTrial.gov (NCT02153047).…”
Section: Methodsmentioning
confidence: 99%
“…In conjunction with the systematic search we found five published study protocols 16-20 . No additional ongoing studies were found in the PROSPERO database 6 .…”
Section: Resultsmentioning
confidence: 99%
“…There are five published study protocols for RCTs evaluating the use of spirometry as a strategy for smoking cessation 16-20 . Results from these studies can be expected to affect the current state of scientific knowledge within a few years.…”
Section: Discussionmentioning
confidence: 99%
“…The heterogeneity of the interventions between previous studies limited the scope to combine the findings with the DOC study in a meta‐analysis. Findings from ongoing trials may help to provide more conclusive evidence as to whether complex interventions including the individualised communication of lung age alongside education and/or nicotine replacement therapy impact on smoking cessation.…”
Section: Discussionmentioning
confidence: 99%
“…There is a paucity of good quality research evidence in this area, and the findings are currently inconclusive . Trials have been set up to consider the effectiveness of complex interventions around lung health, including spirometry, smoking cessation advice, and personalised feedback of lung health, with the results not yet available.…”
Section: Introductionmentioning
confidence: 99%